Penerapan Teknologi Tapat Guna (TTG) Mesin Perontok Padi Pada Kelompok Tani Padi di Kecamatan Cipungara Kabupaten Subang - Kristian Sugandi, Wahyu; Yusuf, Asep; Achirul Nanda, Muhammad (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2025)
Manual rice threshing can result in up to a 10% grain loss because the rice grains are not gathered at a single point. Another drawback of manual threshing is that not all rice grains are separated from their husks due to the need for high-pressure strikes. Additionally, farmers, especially women, often complain of back pain because rice threshing work is carried out all day during the harvest season. To reduce the workload and fatigue experienced by rice farmers in Cipunagara District, Subang Regency, the objective of this Community Service Program (PKM) is to introduce rice threshing machines to partner groups. The method involves implementing rice threshing machine technology, including the allocation of 2 (two) fully mechanical rice threshing machines developed by the Agricultural Machinery Laboratory of Unpad. The accompanying mechanism and socialization involve lectures on post-harvest rice processing, specifically rice threshing, instructions on operating and maintaining rice threshing machines, and concluding with discussions. The results of this PKM show increased farmer knowledge regarding post-harvest rice processing, particularly rice threshing, with reduced grain loss (<2%), shorter threshing time (1 HOK), and a threshing machine capacity of 500 kg/hour.